Word Catheter Placement for Bartholin's Gland Abscess: Applications for Clinical Practice and Simulation. (January 2019) - Lannen, Amy; Destephano, Christopher; Wilbeck, Jennifer
Abstract : For women who present with Bartholin's abscesses, placement of a Word catheter offers a minimally invasive approach for effective management in urgent care and emergency department settings. Although the procedure is relatively simple, the frequency of placement in the ED setting varies. Provider familiarity with both the device and the procedure can be enhanced using simulation techniques. This article presents the diagnostic and treatment approaches to Bartholin's abscesses and describes in detail both low- and high-fidelity simulations for Word catheter placements. Abstract : Supplemental Digital Content is Available in the Text.